Chronic total coronary occlusion: treatment results. (4th July 2017) - Kirk Christensen, Martin; Freeman, Phillip Fischer; Rasmussen, Jeppe Groendal; Villadsen, Anton Boel; Raungaard, Bent; Eggert Jensen, Svend; Thuesen, Leif
Abstract: Objectives . To describe the clinical and procedural coronary chronic total occlusion (CTO) treatment results in a Nordic PCI centre during the implementation of a CTO treatment program. Design . In a retrospective registry study, we assessed; (1) indication for the procedure, (2) Canadian Cardiovascular Society angina pectoris score (CCS)/New York Heart Association (NYHA) heart failure score, (3) lesion complexity and (4) adverse events during hospital stay and three months following the index procedure. Results . The study cohort included 503 patients (594 lesions). From 2010 to 2013 96% of procedures were performed with antegrade wire-escalation technique and 4% performed using retrograde techniques, from 2013–2016 the corresponding numbers were 83% and 17.0%. The procedural success rate was 69%, increasing from 64% before to 72% (p = .06) after routinely using the retrograde approach. No individual patient characteristic, lesion variable or score was strongly associated with procedural success or failure. There were 4% serious procedure related complications. In patients with PCI of a CTO lesion only, 87% were in CCS or NYHA functional class ≥2 before the index procedure vs. 22% at follow-up. Conclusions . Routine use of retrograde techniques tended to increase the procedural success rate. Clinical results after three months were acceptable, but the complication rate was higher than for non-CTO PCI. Individual patient and lesion characteristics had a low predictability for procedural success. Therefore, clinical symptoms, objective signs of myocardial ischemia and procedural risk should be focus points in coronary chronic total occlusion treatment strategies.